An Ayurvedic Approach on Endometritis w.s.r. to Pittaja Asrigdara-A Case Study - Sonu; Dixit, Mahesh; Meena, Narendra Kumar (International Research Journal of Ayurveda & Yoga, 2022)
A woman’s reproductive system is a delicate and complex system in the body. It is important to protect it from infections and injury for their health. Endometritis is inflammation of the uterine lining. It can affect all layers of the uterus and is usually due to an infection. The uterus is typically aseptic nature. However, the travel of microbes from the cervix and vagina can lead to infection. It’s usually not life-threatening, but it’s important to get it treated as soon as possible. It will generally cure when treated. Untreated infections can lead to complications with the reproductive organs, issues with fertility, and other general health problems. A female patient aged 35 years visited OPD of Prasuti Tantra and Stri Roga department of MMM Govt. Ayurved College, Udaipur, with complaints of heavy menstrual bleeding and prolonged menstrual bleeding more than seven days since six months with lower abdominal pain. Patient was given Nagkesharadi churna 3 gm orally BD and Panchtikta ghrita guggulu 2tab BD with lukewarm water.